The global variation of air-earth current at Tirunelveli - Jeeva, K.; Nair, K.U.; Panneerselvam, C.; Gurubaran, S.; Rajaram, R. (My University, 2001)
Air-Earth currents are expected to provide the most stable representation of the Global Electric Circuit system. Current density measurements carried out from the low Latitude Continental Station, Tirunelveli (8.7° N, 77.8° E, 30 m AMSL) have been used for this purpose in the present work. The effects produced by local sources have been identified, and variations on days when the expected global patterns are observed, are reported.
Keywords: Global Electric Circuit system; Air-Earth current; Tirunelveli